From recruitment to enrollment: understanding student-athletes’ college choice decisions - Al-Fattal, Anas; Walker II, Eddie G.; Gust, Anita M. (Frontiers in Sports and Active Living, 2025)
IntroductionThis study investigates the factors influencing student-athletes' college choice in the context of a shifting intercollegiate athletic landscape. While existing research has focused heavily on NCAA Division I athletes, limited attention has been paid to how student-athletes at Division II institutions navigate their enrollment decisions. Drawing on Means-End Theory and Social Exchange Theory, particularly the framework established by Czekanski and Barnhill (2015), this study explores how institutional attributes, athletic opportunities, financial considerations, and socio-emotional dynamics intersect in shaping college decision-making.MethodsUsing a qualitative focus group approach, data were collected from 33 student-athletes at a small Midwestern university. Participants shared their experiences, motivations, and reflections on what mattered most in their college selection process.ResultsSeven key themes emerged: athletic program quality, financial assistance, location and campus, social aspects and support systems, academic and athletic balance, long-term career goals, and diversity and inclusion. Findings reveal that while athletic and financial factors were important, relational and academic dimensions were also central. Name, Image, and Likeness (NIL) opportunities and athletic realignment were acknowledged but not prioritized.DiscussionThe study contributes to a broader understanding of college choice by highlighting how student athletes interpret value through both traditional and evolving lenses. Implications are discussed for athletic recruiters, university administrators, and policymakers aiming to support student-athlete enrollment in a competitive and dynamic environment.